Socio-demographic profile and psychiatric morbidities of suicide attempters: a cross-sectional observation in a tertiary care hospital of Bangladesh - Roy, Jotirmoy; Adiluzzaman, Md Al Fatah Al; Hasan, Md Tanvir; Roy, Dibbya Duty; Qusar, MMA Shalahuddin; Shah, Md Mohsin Ali; Arafat, SM Yasir (Bangladesh Journal of Psychiatry, 2020)
Suicide is a perplexing phenomenon of taking one’s own life. Reasons behind suicide attempts are also unique. Clinical characteristics of these patients have not been adequately studied from a psychosocial and psychiatric point in Bangladesh. This study was aimed to assess the socio- demographic profile and psychiatric morbidities in suicide attempters. This was a descriptive cross sectional study conducted from May 2017 to September 2017. A total of 101 patients were selected purposively who were admitted following suicide attempt in different departments of Rangpur Medical College Hospital (RMCH). Medical officers in the psychiatry department interviewed them by using a semi-structured questionnaire. Diagnosis was made according to DSM-IV. The results showed that the majority of the respondents were socio-economically deprived young persons. Most (42%) of them were <20 years of age with female (53%) preponderance. Among them 51% were unmarried, 73% were rural dwellers 37% were students and 58% attempts were impulsive. Among the respondents 63% had no prior suicidal thoughts, 56% resorted to poisoning, 49% attempted due to domestic quarrel, 65% suffered from psychiatric disorders where major depressive disorder (18%) was found to be one of the commonest diagnosed disorders. Psychiatric disorders and their co- morbidities are common in suicide attempt patients which calls for implementation of hospital guidelines for routine psychiatric and psychosocial assessments. Bang J Psychiatry December 2016; 30(2): 36-40